Chemical Constituents and Antibacterial Activity of Essential Oil of Prangos ferulacea (L.) Lindl. Fruits: Essential oil of Prangos ferulacea - Mohammad Ali Massumi,; Mohammad Reza Fazeli,; Seyed Hamid Reza Alavi,; Yousef Ajani, (Iranian Journal of Pharmaceutical Sciences, 2007)
The essential oil of Prangos ferulacea (Apiaceae) fruits was obtained by hydrodistillation and analyzed by gas chromatography (GC) and GC-mass spectrometery (MS). Among the 39 identified constituents accounting for 99.99% of the total oil, the major components were chrysanthenyl acetate (26.53%), limonene (19.59%), alpha pinene (19.50%), delta-3-carene (6.56%), mesitaldehyde (6.09), and germacrene-B (3.55%). Antimicrobial activity of the essential oil was investigated against some gram positive and gram negative bacteria. The essential oil of P. ferulacea showed activity against Staphylococus aureus, S. epidermis, Eschrechia coli and Pseudomonas aeroginosa.